(3EJMGa GdSYOGA HefGbH SjO GdTgOGAs - (3ejQZfj, Gdecj, GdWGFaj, CHh GdSjGOI, Yaja GdOHf, YHO Gddg Hf EHQGgje Hf MSf Hf eMeO Cejf, J (B1207 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3agPG GJMGa GdSYOGA HefGbH SjO GdTgOGA bOSfG Gddg HCSQGQg hCaGV YdjfG ef HGgQ GfhGQg aGfg GdCSO GdVQZGe hGdHMQ GdYLGL GdWGe Ph GdBjGJ GdYXGe(B...s
(3BNQgG (B:s
.. (3hEdi GdQShd GdpMH CcQe ecQe Udi Gddg Ydjg aj GdBfGA (B*** (3hYdi GdUMGH hBdg eG ReReJ ddYGTbjf lMOGJge HMeGA (B... (3gPG BNQ eG bUOJgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\64s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJGQjNs